1987
DOI: 10.1192/bjp.150.2.161
|View full text |Cite
|
Sign up to set email alerts
|

Nuclear Magnetic Resonance Brain Imaging in Chronic Schizophrenia

Abstract: Patients with chronic schizophrenia were examined by nuclear magnetic resonance imaging of the brain. Subgroups of the syndrome with high positive or high negative symptom scores and ventricular dilatation were compared with each other and with normal controls in respect of regional spin lattice relaxation time (T1) changes. Significant differences were not observed between the schizophrenic subgroups and controls but there were significant differences between the subgroups themselves. The presence of tardive … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
14
2
2

Year Published

1988
1988
2001
2001

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 73 publications
(18 citation statements)
references
References 15 publications
0
14
2
2
Order By: Relevance
“…The mean pretreatment ( f 1 SD) T I and T2 values for white matter were 450 (9) and 73 (3) respectively. These values from the thalamus were 675 ( 13) and 83 (2). No significant change was found in either T I or T2 at any time after the commencement of methylprednisolone.…”
Section: Resultsmentioning
confidence: 82%
See 1 more Smart Citation
“…The mean pretreatment ( f 1 SD) T I and T2 values for white matter were 450 (9) and 73 (3) respectively. These values from the thalamus were 675 ( 13) and 83 (2). No significant change was found in either T I or T2 at any time after the commencement of methylprednisolone.…”
Section: Resultsmentioning
confidence: 82%
“…Such alterations have been reported in most brain disorders, for example multiple sclerosis (MS) ( l o ) , dementia ( 3 ) , and schizophrenia (2). The measurement of T I and T2 is a potentially valuable means of monitoring the influence of drug treatment on the natural history of brain abnormalities in patients with these conditions.…”
Section: Introductionmentioning
confidence: 99%
“…(We have also recently found a relationship between third ventricle enlargement and reduced premorbid heart rate levels in the same subjects, suggesting that third ventricle enlargement is related to a generalized deficit in excitatory autonomic acitivty (48).) These findings are of interest particularly in light of evidence linking decreased autonomic responsiveness and ventricular enlargement to the negative symptom complex (49)(50)(51)(52)(53)(54)(55)(56)(57)(58). It is important to note that not all studies have found significantly more negative symptoms in schizophrenics who are electrodermal nonresponders or who have enlarged ventricles (34,(59)(60)(61)(62)(63)(64)(65)(66).…”
Section: Etiological and Phenomenological Variabilitymentioning
confidence: 96%
“…Previous reports of the project found that the interaction of genetic risk for schizophrenia and delivery complications significantly predicted the adult ventriculomegaly scores of the sample (17, 28), and that enlargement of the third ventricle was related to a significant reduction in ANS responsiveness measured during adolescence (47,48). Other work with schizophrenics has independently linked a preponderance of negative symptoms to electrodermal nonresponsiveness and to enlargement of the ventricular system (49)(50)(51)(52)(53)(54)(55)(56)(57)(58). These findings suggest that perinatal damage to diencephalic and/or limbic structures involved in excitatory autonomic functioning may be part of the basis of predominantly negative-symptom schizophrenia.…”
Section: An Empirical Testmentioning
confidence: 99%
“…Mais de cem artigos foram selecionados e, entre eles, 59 eram estudos que relacionaram psicopatologia com neuroimagem estrutural na esquizofrenia. Destes, 16 foram incluídos nas duas metanálises 1,6,[22][23][24][25][26][27][28][29][30][31][32][33][34][35] e três foram incluídos somente na metanálise II [36][37][38] (Tabelas 1 e 2). Quarenta estudos foram considerados relevantes, mas não foram incluídos devido à impossibilidade de extração de dados (disponíveis se requisitados ao primeiro autor).…”
Section: Resultsunclassified